Pola Pembelian Produk Bangunan Menggunakan Algoritma FP-GROWTH pada PT Dharmaputra Jaya Bersama - Deryl Andeya Yeremia; Mardiani Mardiani (MDP Student Conference, 2026)
PT Dharmaputra Jaya Bersama is a company engaged in the sale of building materials such as nails, cement, sand, and ceramics, located in Palembang, South Sumatra. To improve the efficiency of sales strategies an inventory management, the company requires an analytical system capable of identifying customer purchasing patterns based on transaction data. This analysis applies data mining techniques using the FP-Growth algorithm to discover associations between products thatare frequently purchased together. The results can support decision-making in inventory control and sales strategies. By utilizing this approach, the company is expected to enhance operational efficiency, minimize overstocking or stockouts, and design more accurate promotional efforts based on customer purchasing behavior.